Out of the Running : Why Millennials Reject Political Careers and Why It Matters - Shames, Shauna Lani (Book collections on Project MUSE., 2017)
Millennials are often publically criticized for being apathetic about the American political process and their lack of interest in political careers. But what do millennials themselves have to say about the prospect of holding political office? Are they as uninterested in political issues and the future of the American political system as the media suggests? Out of the Running goes directly to the source and draws from extensive research, including over 50 interviews, with graduate students in elite institutions that have historically been a direct link for their graduates into state or federal elected office: Harvard Law, Harvard's Kennedy School of Government, and Boston's Suffolk University Law School. Shauna Shames, herself a young graduate of Harvard University, suggests that millennials are not uninterested; rather, they don't believe that a career in politics is the best way to create change. Millennials view the system as corrupt or inefficient and are particularly skeptical about the fundraising, frenzied media attention, and loss of privacy that have become staples of the American electoral process. They are clear about their desire to make a difference in the world but feel that the "broken" political system is not the best way to do so--a belief held particularly by millennial women and women of color. The implications of Shames' argument are crucial for the future of the American political system--how can a system adapt and grow if qualified, intelligent leaders are not involved? An engaging and accessible resource for anyone who follows American politics, Out of the Running highlights the urgent need to fix the American political system, as an absence of diverse millennial candidates leaves its future in a truly precarious position.